Circular RNA hsa_circ_0072995 promotes breast cancer cell migration and invasion through sponge for miR-30c-2-3p. (4th September 2018) - Zhang, He-Da; Jiang, Lin-Hong; Hou, Jun-Chen; Zhou, Si-Ying; Zhong, Shan-Liang; Zhu, Ling-Ping; Wang, Dan-Dan; Yang, Su-Jin; He, Yun-Jie; Mao, Chang-Fei; Yang, Yong; Wang, Jin-Yan; et al.
Aim: To study the role of hsa_circ_0072995 in regulating the invasion and migration of breast cancer cells.Materials & methods: Hsa_circ_0072995 expression was confirmed by quantitative real-time PCR; evaluating the migration and invasion of breast cancer cells through transwell assay; predicating circRNA/microRNAs interaction using the miRanda and RNAhybrid software; identifying the relationship between hsa_circ_0072995 and miR-30c-2-3p by luciferase activity assay; detecting the location of hsa_circ_0072995 by Fluorescence in situ hybridization assay.Results: Hsa_circ_0072995 was significantly upregulated in MDA-MB-231 cells compared with MCF-7 cells. Hsa_circ_0072995 regulated the invasion and migration of breast cancer cells. Hsa_circ_0072995 existed in the nucleus and cytoplasm, and the proportion of the two was roughly equal. Hsa_circ_0072995 bound to miR-30c-2-3p. Overexpression of miR-30c-2-3p inhibited breast cancer cells migration and invasion. Low expression of miR-30c-2-3p was correlated with poor overall survival by The Cancer Genome Atlas database.Conclusion: Hsa_circ_0072995 may be a novel biomarker for breast cancer, and may function in metastasis of breast cancer.